Web-based Environment Monitoring System (Case Sudy: Laboratory of Universitas Multimedia Nusantara) - Fahmy Rinanda Saputri; Vanessa Lee (Universitas Islam Raden Rahmat, Malang, 2023)
Green building is the concept of designing, building, operating, and maintaining buildings that pay attention to the use of natural resources, indoor air quality, and the health of the occupants. This green building is the choice in responding to the issue of limited non-renewable energy. To monitor the environmental conditions of green buildings, a sensor system is needed to maintain environmental conditions according to standards. This study aims to design a sensor system to monitor environmental conditions in Universitas Multimedia Nusantara. A real-time monitoring system is needed to maintain the green building environment's condition. The results of the study succeeded in designing a real-time monitoring system for green building environmental sensors, especially web-based classrooms using the NodeMCU ESP8266, DHT22 Sensor, and LDR Sensor. The difference in readings between the monitoring sensor system and the environment meter for lighting levels, temperature, and humidity respectively is 0.67 lux, 0.9°C, and 5.8%RH.